Aortic Dissections Type A during Sexual Intercourse in Male Patients: Accident or Systematic Coincidence? Examination of 365 Patients with Acute Aortic Dissection within 20 Years - Gansera, Laura; Deutsch, Oliver; Szameitat, Larissa; Eichinger, Walter; Gansera, Brigitte (The Thoracic and Cardiovascular Surgeon, 2016)
Objectives Physical exercise accompanied by arterial hypertension is known to trigger acute aortic dissections. As a booster effect, mental stress leads to aggravation of hypertensive crisis. The aim of the study was to evaluate whether stress factors during sexual intercourse play any role as a catalyst in patients with acute type A aortic dissections. Concerning this subject, only two case reports have been published.Methods A total of 365 patients with acute type A aortic dissections, operated between January 1993 and July 2014, were analyzed retrospectively. The main focus was to identify the provoking situation before onset of symptoms. A total of 247 patients were males and mean age was 60.2 years (range, 17.0–91.9 years). Of the total cohort, 86 patients (24%) were younger than 50 years (68 males) and 184 patients (50%) were younger than 60 years (149 males).Results The explicit trigger could not be determined in 24% of the patients. In majority of the patients, onset of symptoms occurred during physical exercises, such as sports or lifting of heavy weights (68%), without a significant difference between males and females. In only 8% of the patients, symptoms occurred at rest. In 0.9%, Marfan syndrome was evident. Eleven of 68 males < 50 years (16%) and 17 of 149 males < 60 years (11%) but none among females (p = 0.03) experienced sudden onset of symptoms during sexual intercourse.Conclusion Combined physical and emotional stress during sexual intercourse seems to present a meaningful promoter effect for acute aortic dissections, especially in younger males, but not in females. Despite self-evidence of this phenomenon, frequency of this sensitive issue appears to be surprisingly high.
Keywords: aortic dissections; sexual intercourse; gender aspects